A study of the collection development practices of selected government hospital libraries in Quezon City - Perocho, Kathrina T.; Rosal, Rosvida R. (Quezon City : Institute of Library and Information Science, University of the Philippines Diliman, 2004)
This study was conducted to determine the collection development practices of six government hospital libraries in Quezon City and the factors that affect the collection development activity. To do this, the following components of the collection development process were closely analyzed - community analysis, formulation of collection development policies, selection and acquisition, collection evaluation and weeding.
This study carried out a descriptive survey method of inquiry. Survey questionnaires were handed out to the librarians of the six libraries studies. Interviews were conducted and documents such as annual reports and library reports were consulted for relevant information.
Findings revealed the factors that affect collection development in government hospital libraries. These include library budget, number of staff, presence of written collection development policies and hospital administration support. Recommendations include the provision of adequate library budget, more staff support, formulation of written collection development policies and greater hospital administration support. It is also recommended that the libraries participate in resource sharing activities to further enhance their collection.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Hospital libraries -- Philippines -- Quezon City; Public hospitals -- Philippines -- Quezon City